Numerical Study of the Torque and Power of a Hydraulic Turbine with Oscillating Blades - Rositsa Velichkova; Rosen Iliev; George Pichurov; Detelin Markov; Iskra Simova; Martin Pushkarov; Tsvetan Tsalov (Energies, 2023)
This paper presents results from a physical and numerical study of a new type of axial hydraulic turbine with oscillating blades, which is used to utilize wind waves energy. The pilot studies were conducted on a test bench constructed in one of the labs of the “Department of Hydrodynamics and Hydraulic Machines” in the Technical University of Sofia. The numerical computations were performed with the commercial software package Ansys Fluent 2022. The flow has been modeled with the k-ω (SST) turbulence model, whose main advantage is to resolve the viscous sublayer in over refined meshes. A pressure-based solver was used since the fluid is incompressible and the flow velocity is low. The study investigated several different pitch angles of the blades ranging between 0 and 80 deg at prescribed upstream flow velocities from 0.15 m/s to 2.0 m/s. The dependencies of the torque coefficient, power coefficient, and the optimal tip speed ratio on the flow velocity are presented and discussed.